Viewpoint geosites — values, conservation and management issues - Migoń, Piotr; Pijet-Migoń, Edyta (Proceedings of the Geologists' Association, 2017)
Viewpoint geosites are a specific category of geosites, defined as locations which allow for unobstructed observation of the surrounding landscape and comprehension of Earth history recorded in rocks, structures and landforms visible from this locality. They have been poorly addressed in literature so far and this paper, primarily based on field observations and literature review, aims to discuss their significance and associated management and geoeducation issues. Viewpoint geosites do not necessarily have an intrinsic value related to geology or geomorphology but offer a view towards features and areas which do have such values. The role of a viewpoint geosite may be played by both natural features such as tors, crags, mountain tops, cliff edges, as well as by man-made structures erected intentionally to provide panoramic views and converted to play such a role. Paradoxically, although viewpoint geosites are the most suitable places to develop landscape interpretation, any interpretation facilities may severely interfere with the natural scenery, spoiling the aesthetic qualities of the landscape. Publications and mobile applications are alternative means to develop interpretation programmes. As other types of geosites, viewpoint geosites require management strategies that should focus on sustaining the view by periodic removal of vegetation if necessary, getting right balance between on-site facilities and scenic values, preventing soil erosion, and ensuring visitor safety.